Lost in the storm: The academic collaborations that went missing in hurricane Isaac - Raquel Campos; Fernanda Leite Lopez de Leon; Ben McQuillin (University of Kent, School of Economics, 2017)
By exploiting the cancellation of the 2012 American Political Science Association Annual Meeting, we investigate the role of conferences in facilitating academic collaboration. We assembled datasets comprising 17,468 academics and 86 million pairs of conference participants. In difference-in-differences analysis, we find the conference cancellation led to a decrease in individuals' likelihood of co-authoring an article with another attendant by 18 percent. Moreover, collaborations formed among attendants of (occurring) conferences are associated with more successful co-publications: an effect which is sharpest for teams that are new or non-collocated. These findings are novel and demonstrate the importance of conferences in scientific production.
Keywords: O31; I23; D02; 330; conference effects; collaboration; formation of teams; production in science